Percutaneous antegrade transarterial treatment of traumatic radial arteriovenous fistula - Kudret Keskin; Ayhan Olcay; Fatih Eren (KARE Publishing, 2013)
Traumatic arteriovenous fistulas (AVF) are almost exclusively the result of penetrating trauma and there is usually a history of hemorrhage. Typically, the patient demonstrates a thrill and bruit over the site of injury. We report a woman who presented with longstanding pain and swelling of the right hand due to radial AVF that possibly occurred following an injury to the right hand that happened 10 years prior to the date of admission. Since surgery was considered high risk due to multiple fistulas and previous surgery, percutaneous coil embolization was performed via the ipsilateral antegrade radial approach.